Cobalt Phosphide Ultrathin and Freestanding Sheets Prepared through Microwave Chemical Vapor Deposition: A Highly Efficient Oxygen Evolution Reaction Catalyst. Issue 21 (8th November 2019) - Rafai, Souleymen; Qiao, Chen; Wang, Zhitao; Cao, Chuanbao; Mahmood, Tariq; Naveed, Muhammad; Younas, Waqar; Khalid, Syed
Abstract: The oxygen evolution reaction (OER) is the prime barrier for many appealing energy conversion and storage technologies, including water electrolysis, metal–air batteries, and fuel cells. Therefore, developing a cost‐effective, efficient, and robust OER catalyst is still a challenge. Herein, we report a fast, low‐cost, and gram‐scale approach to overcome the synthesis of freestanding, ultrathin (ca. 1.3 nm), and mesoporous CoP sheets through the microwave‐assisted growth of a cobalt‐layered double hydroxide (Co‐LDH) precursor coupled with chemical vapor deposition. The present 2D nanostructure not only guarantees a rich surface of active sites, but also promotes the charge and mass transfers due to the ultrathin and mesoporous features that allow it to efficiently perform the OER. It was found that the surface of the CoP sheets was oxidized in situ under the catalytic conditions, suggesting that Co3 O4 /CoP is effectively the active form of the catalyst, thereby modulating the electronic structure of Co atoms (active centers). This was embodied by the lowering of the Co‐LDH's required overpotential to achieve 10 mA cm −2 (η10 ) from 296 to 265 mV and the Tafel slope decrease from 75 to 63 mV dec −1 upon phosphorization. Such performances of CoP nanosheets are remarkably superior to those of commercial RuO2 and compare favorably to the best values reported for noble‐metal‐free OER electrocatalysts. Abstract : Top CoP : A microwave‐assisted method is developed for the gram‐scale synthesis of ultrathin, mesoporous, and freestanding CoP sheets. Such nanostructure maximizes the number of surface exposed atoms and enables fast mass and charge transfers. Therefore, the as‐prepared CoP exhibits an auspicious electrocatalytic activity toward oxygen evolution reaction.